A nondigestion extraction method for boron in plant leaves - Correa, Antonio E.; Miyazawa, Mario; Pavan, Marcos A. (Pesquisa Agropecuaria Brasileira, 2014)
A nondigestion procedure using HCl for the extraction of B in plant tissues is described. Plant materials were treated with 1NHCl, heated at 80°C for 15 minutes, shaken at 250 rpm for 60 minutes, and filtered. Then, 5 ml of the extracted solution was treated with 100 mg of activated charcoal, shaken at 250 rpm for 15 minutes, and refiltered. Boron was determined by the colorimetric azomethine-H method. The results were compared with those obtained by dry-ashing method. B contents were determined by the colorimetric method with azomethine-H. The results have shown that both methods extracted identical quantities of B. B adsorption by activated-charcoal in an acid-medium was minimum. The presence of activated charcoal in the nondigested leaves extract carried out the complete adsorption of the soluble substances interfering with B colorimetric determination at 420 nm. The mean B extraction accuracy by the proposed method was 1.54 percent.